AID induces intraclonal diversity and genomic damage in CD86+ chronic lymphocytic leukemia cells. Issue 12 (18th October 2014) - Huemer, Michael; Rebhandl, Stefan; Zaborsky, Nadja; Gassner, Franz J.; Hainzl, Stefan; Weiss, Lukas; Hebenstreit, Daniel; Greil, Richard; Geisberger, Roland
Abstract : The activation‐induced cytidine deaminase (AID) mediates somatic hypermutation and class switch recombination of the Ig genes by directly deaminating cytosines to uracils. As AID causes a substantial amount of off‐target mutations, its activity has been associated with lymphomagenesis and clonal evolution of B‐cell malignancies. Although it has been shown that AID is expressed in B‐cell chronic lymphocytic leukemia (CLL), a clear analysis of in vivo AID activity in this B‐cell malignancy remained elusive. In this study performed on primary human CLL samples, we report that, despite the presence of a dominant VDJ heavy chain region, a substantial intraclonal diversity was observed at VDJ as well as at IgM switch regions (Sμ), showing ongoing AID activity in vivo during disease progression. This AID‐mediated heterogeneity was higher in CLL subclones expressing CD86, which we identified as the proliferative CLL fraction. Finally, CD86 expression correlated with shortened time to first treatment and increased γ‐H2AX focus formation. Our data demonstrate that AID is active in CLL in vivo and thus, AID likely contributes to clonal evolution of CLL.